Towards an estimation of sub-sea-ice platelet-layer volume with multi-frequency electromagnetic induction sounding. Issue 69 (2015) - Hunkeler, Priska A.; Hendricks, Stefan; Hoppmann, Mario; Paul, Stephan; Gerdes, Rüdiger
Abstract: Ice-platelet clusters modify the heat and mass balance of sea ice near Antarctic ice shelves and provide a unique habitat for ice-associated organisms. The amount and distribution of these ice crystals below the solid sea ice provide insight into melt rates and circulation regimes in the ice-shelf cavities, which are difficult to observe directly. However, little is known about the circum-Antarctic volume of the sub-sea-ice platelet layer, because observations have mostly been limited to point measurements. In this study, we present a new application of multi-frequency electromagnetic (EM) induction sounding to quantify platelet-layer properties. Combining in situ data with the theoretical response yields a bulk platelet-layer conductivity of 1154 ± 271 mS m –1 and ice-volume fractions of 0.29-0.43. Calibration routines and uncertainties are discussed in detail to facilitate future studies. Our results suggest that multi-frequency EM induction sounding is a promising method to efficiently map platelet-layer volume on a larger scale than has previously been feasible.